Organización Contable en la “Distribuidora Amable Camacho LojaGas”, del Sr. Camacho Soto Amable Mirabel de la Ciudad de Yantzaza, período 01 de abril al 30 de junio 2024. - Jiménez Jiménez, Gyssel Estefania (2024)
The Curricular Integration Work was developed due to the need to provide real economic- financial information about the course of its daily activities to its owner Mr. Amable Camacho, in addition to being a prerequisite for obtaining the Bachelor's Degree in Accounting and Auditing. Therefore, for the execution, a thorough analysis of the documentation provided was carried out and a plan and manual of accounts adjusted to the needs and according to the activities of the business, in which each one was classified and described. of the accounts of assets, liabilities, equity, income, costs and expenses with their respective coding that allowed the recognition of each one. Then we proceeded to develop the Accounting Process that, thanks to the source documentation and physical verification of the assets, rights and obligations, the Initial Inventory and the Initial Statement of Situation were prepared, determining the assets, liabilities and equity at the start date of the accounting year. . Then the Daily Book was made based on the activities and operations of the company, keeping control of the merchandise through a permanent account system. In addition, auxiliary books were designed in order to keep control of the cash that enters and leaves; They were subsequently transferred to the General Ledger, classifying each account with their respective balances that were useful for the preparation of the Trial Balance, Worksheet and finally the Financial Statements, where the Income Statement determined a total income of $10,556.61, a total of expenses $18,689.35 generating a Loss for the year from April 1 to June 30, the 2024 of $8,132.74; the Balance Sheet with total assets of $257,500.94, liabilities of $80,272.28 and equity of $177,228.66.